2012
DOI: 10.1186/1476-9255-9-26
|View full text |Cite
|
Sign up to set email alerts
|

18FDG PET-CT imaging detects arterial inflammation and early atherosclerosis in HIV-infected adults with cardiovascular disease risk factors

Abstract: BackgroundPersistent vascular inflammation has been implicated as an important cause for a higher prevalence of cardiovascular disease (CVD) in HIV-infected adults. In several populations at high risk for CVD, vascular 18Fluorodeoxyglucose (18FDG) uptake quantified using 3D-positron emission-computed tomography (PET-CT) has been used as a molecular level biomarker for the presence of metabolically active proinflammatory macrophages in rupture-prone early atherosclerotic plaques. We hypothesized that 18FDG PET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…In a proof of concept study, 9 HIV-infected individuals with suppressed viremia on ART were compared to 5 HIV-negative individuals and were shown to have higher 18 FDG uptake in the carotid arteries (77). In another cross-sectional study, 27 HIV-infected individuals were compared to two non-HIV-infected control groups, one matched for age, sex, Framingham risk score, and without atherosclerotic disease, the other matched on gender but with known atherosclerotic disease (78).…”
Section: Hiv and Cvd Riskmentioning
confidence: 99%
“…In a proof of concept study, 9 HIV-infected individuals with suppressed viremia on ART were compared to 5 HIV-negative individuals and were shown to have higher 18 FDG uptake in the carotid arteries (77). In another cross-sectional study, 27 HIV-infected individuals were compared to two non-HIV-infected control groups, one matched for age, sex, Framingham risk score, and without atherosclerotic disease, the other matched on gender but with known atherosclerotic disease (78).…”
Section: Hiv and Cvd Riskmentioning
confidence: 99%
“…10, 11 Recent imaging studies have added to our understanding of the relationship between immune activation and atherosclerotic inflammation in HIV. In studies that employed FDG-PET/CT, individuals with HIV have been shown to have higher levels of atherosclerotic inflammation compared to non-infected controls 12, 13 . One such study showed that the atherosclerotic inflammation correlates with markers of monocyte activation.…”
mentioning
confidence: 99%
“…Yarasheski et al 30 have detected differences in vascular inflammation and early atherosclerosis between HIV-infected adults with CVD risk factors and healthy HIV-seronegative controls with 18 F-FDG-PET/CT imaging. These findings confirm the utility of the molecular-level imaging approach to detecting and quantifying glucose uptake in inflammatory macrophages present in metabolically active, rupture-prone atherosclerotic plaques in HIV-infected adults, a population with increased CVD risk.…”
Section: Cardiovascular Diseasementioning
confidence: 98%